Rediscovery of Geophila repens (L.) I.M. Johnst. (Rubiaceae) in Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2018)
Abstract not availableJahangirnagar University J. Biol. Sci. 7(2): 121-125, 2018 (December)